PENGARUH PENGGUNAAN JENIS ECU (ELECTRONIC CONTROL UNIT) DAN JENIS CENTRIFUGAL CLUTCH TERHADAP PERFORMA MESIN 150 CC: THE INFLUENCE OF USING THE TYPE OF ECU ELECTRONIC CONTROL UNIT) AND THE TYPE OF CENTRIFUGAL CLUTCH ON 150 CC ENGINE PERFORMANCE - Wisnu, Hafid (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2023)
ECU is an electronic device for controlling electronic systems on motorcycles. Centrifugal clutch uses centrifugal force to connect the engine to the wheels. Selection of the right ECU and centrifugal clutch can improve engine performance. This study compares engine performance using different ECUs and centrifugal clutches on Honda Vario 150cc motorcycles. The research method uses experiments and data analysis. The results show that the use of a racing ECU produces the best power at 3500 rpm, which is 14.43 hp with standard clutch lining. Power increase of 1.53 hp from standard conditions. The best acceleration of 9.4 hp is achieved with a racing ECU and a modified clutch pad (7 cm long). At high speed, the highest power reaches 11.93 Hp at 7500 rpm with a modified clutch lining (length 7 cm). The best torque is 42.22 Nm at 1500 rpm with a racing ECU and modified clutch lining (7 cm long), an increase of 2.4 Nm from the standard 39.82 Nm..